Fluid-Structure Interaction (Fsi) And Sediment Transport Study Of Tnb Hydropower Station - Yusof, Wan Putera Saidina Umar Wan (Universiti Sains Malaysia, 2019)
During ancient times, the dam is built solely for water supply however as humans evolves, the function of the dam also increased in order to fulfil human needs. As time passing, a problem has aroused which causing a lot of difficulties at the dam. The problem is caused by the sediment. Sedimentation will affect the dam in various things such as the safety of dams and reduces energy production, storage, discharge capacity and flood attenuation capabilities. The purpose of this research is to study the movement of the sediment transportation at the TNB hydropower station at Chenderoh Dam. The scaled down model is constructed using the SolidWorks and then it is fabricated to the physical model. The simulation of 3D model is carried out using ANSYS Fluid Structural Interaction. The formulation used is Discrete Particle Method (DPM), Discrete Element Method (DEM) and Navier-Stokes respectively. Particle image velocimetry experiment will also be conducted to verify the simulation results. Finally, the results such as velocity and flow direction are compared, acknowledging the great similarity between numerical simulation and experimental test. Also, in this study, the chemical properties of the sediment and its size are found. Moreover, the scouring rate also being discussed in this research. The highest percentage error between simulation and PIV is 4.89%. Additionally, the highest scouring rate is 4.20E-9 kg/s while highest deposition rate is 2.00E-6 kg/s. According to the findings, the period for a maintenance needs to be done is every 8.9 years. These results will serve as a basis to improve the sediment transportation at Chenderoh Dam in the future.